INFLUENCE OF THE ORAL HYGIENE HABITS IN THE LONGEVITY OF ADHESIVE RESTORATIONS, A LIVE STUDY - Armas Vega, Ana del Carmen (2017)
Objectives. To assess whether the establishment and execution of regular oral hygiene habits, measured through the visible plaque index and gingival bleeding index, influenced the durability of adhesive restorations performed in children between 4-8 years old who accomplished inclusion and exclusion criteria previously determined.Materials and methods. Restorations with adhesive materials were executed according to the split-mouth criteria using two techniques of carioso tissue removal. Parents and children involved in the study received motivation, training and devices of oral toilet on a permanent way, with accompanying each month.Evaluation of gingival health index and the state of restorations using FDI criteria were performed before the intervention, immediately completed restorative processes, at 6 and 12 months. The data collected were subject to descriptive analysis and them interaction between variables, through graphs of estimated densities, diagrams of dispersion an